STUDI KELAYAKAN TEKNIS ABU TEMPURUNG KELAPA SEBAGAI BIO FILLER PADA LAPISAN AC-WC SPESIFIKASI BANDAR UDARA - Alam, Riza Yahya; Fisaini, Juliana; Taufiq, Luthfi Chaliqi (Jurusan Teknik Sipil, Fakultas Teknik, Universitas Syiah Kuala, 2024)
The surface layer of flexible pavement is composed of coarse aggregate, fine aggregate, filler, and asphalt. Generally, the filler material used in flexible pavements is stone ash or cement. However, the continuous use of cement raises concerns about the potential depletion of cement resources in the future. Bio-materials, such as coconut shell ash, offer an alternative option for filler due to the abundance of this waste. To ensure that coconut shell ash can be used as filler, it is necessary to evaluate it according to KP Regulation 14 of 2021 concerning the Technical Specifications for Airport Airside Facilities. The test method employed is the Marshall method, using aggregate gradation and Marshall characteristics for aircraft weighing more than 60,000 lbs, in accordance with KP Regulation 14 of 2021. Coconut shell ash was substituted at varying levels of 2%, 3.5%, 5%, 25%, 50%, and 100% of the filler. The results of this research show that the higher the amount of coconut shell ash substituted, the higher the stability and flow. However, the flow value was too high and exceeded the allowable limit. Therefore, only the 2% variation of coconut shell ash satisfied all Marshall parameters.